Nephrotic syndrome complicating cyanotic congenital heart disease: A report of two cases (2008)
BACKGROUND: Renal complications are said to be common in cyanotic congenital heart disease (CCHD), but have not been documented frequently in Nigerian children. Nephrotic syndrome (NS) is an uncommon complication of CCHD. OBJECTIVES: To report two cases of NS complicating CCHD who presented within months of each other, in order to draw attention to the problem. METHODS: The details of the clinical presentation, course and outcome of two children with CCHD, presenting with features of NS within months of each other, were reviewed. The patients were fully assessed clinically and were further investigated with chest X-ray, ECG ad echocardiography. RESULTS: A 12-year old girl with Fallot’s tetralogy underwent a Blalock-Taussig shunt at the age of 2 years, but subsequently defaulted from follow-up. She reappeared 10 years later with features of NS. Echocardiography revealed impaired myocardial function. Despite initial clinical improvement following three plasma exchanges and Enalapril therapy, she suddenly died on the 15th day of admission. The second patient was a 7-year old boy with tricuspid atresia, diagnosed at the age of 10 months, and similarly defaulted, reappearing six years later with features of NS. Oedema regressed with similar treatment, but his renal function deteriorated. He was stable enough to be discharged after six weeks on admission. CONCLUSION: Proteinuria is likely to be more common in Nigerian children with CCHD than has been previously appreciated. Early intervention in patients with CCHD is desirable in order to prevent development of complications which worsen the prognosis. Patients with CCHD should be screened regularly for proteinuria in order to detect and address renal complications early.